2014
DOI: 10.1179/1476830514y.0000000128
|View full text |Cite
|
Sign up to set email alerts
|

Brain effects of the lectin fromCanavalia ensiformisin adult rats previously suckled in favorable and unfavorable conditions: A spreading depression and microglia immunolabeling study

Abstract: Attenuation in CSD propagation and microglia reaction was associated in adulthood with ConA treatment during brain development, indicating that the lectin can affect the electrophysiological and microglial development, and suggesting long-lasting protective action of the lectin on the rat brain, which is not impeded by the unfavorable suckling condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated the ability of substances that facilitate the spread of CSD, such as monosodium glutamate [ 40 ] and tianeptine [ 41 ], and other compounds that prevent the spread of this electrophysiological phenomenon, such as lectins [ 42 ]. In particular, ethanol has different effects depending on the concentration or exposure frequency, that can facilitate the CSD, and this justifies the higher CSD velocity in cachaça -group rats treated.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the ability of substances that facilitate the spread of CSD, such as monosodium glutamate [ 40 ] and tianeptine [ 41 ], and other compounds that prevent the spread of this electrophysiological phenomenon, such as lectins [ 42 ]. In particular, ethanol has different effects depending on the concentration or exposure frequency, that can facilitate the CSD, and this justifies the higher CSD velocity in cachaça -group rats treated.…”
Section: Resultsmentioning
confidence: 99%
“…This lectin caused a potentiation of the fluoxetine action, a selective serotonin reuptake inhibitor, leading to a decrease of the mouse immobility time during forced swimming tests [ 163 ]. Furthermore, rats treated with the Canavalia ensiformis concanavalin A dose-dependently demonstrated a velocity decrease of the cortical spreading depression propagation and an increase of the amplitude and the duration of the cortical spreading depression potential [ 164 ].…”
Section: Biotechnological Potentialmentioning
confidence: 99%
“…Concanavalin-A (ConA)-induced acute liver injury is a well-established experimental model of immune cells resembling the autoimmune and viral hepatitis in humans [10]. ConA is a plant lectin obtained from Canavalia brasiliensis that induces hepatitis in experimental models by activating T-cells and the release of many inflammatory cytokines (IFN-γ, TNF-α and IL-6) by stimulating Kuppfer cells [11,12]. Overproduction of these inflammatory mediators causes asymptomatic increase in liver transaminase enzyme levels as well as serum proteins, the principal indicators of liver injury [13].…”
Section: Introductionmentioning
confidence: 99%